(untitled) (Perner’s Contacts, 2012)
In connection with the requirement of harmonization of qualification requirements for the posts in the crew inland navigation in the context of improving service quality and safety of navigation of the system design are presented theoretical training and practical training of candidates for the position of the ship’s crew through training modules as part of lifelong learning.